Neorealist theory in international relations: (Kenneth Waltz), for example - Hassan, Najmalddin Faris (Journal of Legal and Political Studies, 2024)
Neorealist theories, although they are an extension of classical realism in international Politics, also differ in thinking. It focuses on the role and activity of international figures in the field of international Politics and the influence of the major powers in the world on the direction and dominance of global Politics. In neorealism, the individual is not aggressive and the system creates chaotic conditions in international Politics due to the lack of a world government to regulate the behavior and command of states in order to advance its hegemony and interests. Neorealism examines the division of powers and its impact on the direction of global order and Politics, and its positive and negative impact on the state of global peace and security. The division of powers and their influence on the formation of different poles and the unipolar, multipolar and bipolar world in their research has a special importance and place for determining global peace and security and international political and economic stability. The research on which polarization is better and which small countries are not under constant threat and its impact on the direction of the economy and global Politics is significant. All this is reflected in their research, and based on their beliefs, this study was conducted.
Keywords: neorealist theory; classical realist theory; individual; polarization; chaos